Sumář dobré praxe Zkušenosti s inzkluzivním vzděláváním - Kissová, Lenka (Masaryk University Press, 2021)
Title in English: Summary of Best Practice : Experiences in Inclusive Education An inclusive school strives to involve all actors in the life of the school. Management, faculty, assistants and counselors, pupils, parents and carers are all seen as important partners in education and upbringing. The basis of this partnership is mutual trust and belief in a common goal - the development of the educational potential and personality of each student. The school, which manages to build a positive climate, thus provides a pleasant environment in which all actors feel good and are themselves interested in participating in the life of the school. The publication is based on the best practice of schools in the Czech Republic. We convey their experiences, the challenges they faced and the ways in which they dealt with them. The Summary contains interesting ideas, tips for specific activities and proven measures.